Atrial tachycardia occurring after a prior atrial fibrillation ablation procedure: Does non-inducibility matter? - O’Neill, Louisa; De Becker, Benjamin; De Smet, Maarten; Le Polain De Waroux, Jean-Benoit; Tavernier, Rene; Duytschaever, Mattias; Knecht, Sebastien (Frontiers in Cardiovascular Medicine, 2022)
Recurrent atrial tachycardia (AT) is a common phenomenon after catheter ablation for AF, particularly in the setting of additional substrate ablation, with many studies demonstrating gap related macro re-entrant AT (predominantly mitral and roof dependent) to be dominant mechanisms. Although multiple inducible ATs after ablation of the clinical AT are commonly described at repeat procedure, the optimal ablation strategy and procedural endpoints are unclear in this setting. A recent randomized study addressing the question of non-inducibility as a procedural endpoint demonstrated no additional benefit to ablation of all induced, non-clinical ATs but was limited by small numbers and high rates of non-inducibility. Nevertheless, once ablation of the clinical AT has been successfully performed, ensuring durable linear block and PV isolation may be sufficient for the prevention of further AT. Durable linear block, particularly at the mitral isthmus, is difficult to achieve but may be facilitated by real-time evaluation of lesion quality and contiguity as well as the novel technique of vein of Marshall ethanol infusion. Large-scale, randomized trials are needed, nonetheless, to fully assess the optimal ablation strategy in the setting of recurrent AT post AF ablation.